Potentials of direct container transshipment at container terminals - Nicole Nellen; Ann-Kathrin Lange; Carlos Jahn (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: On the one hand, the increasing growth in vessel size and land-based capacity constraints raise the need for optimizing the layout and process design at container terminals. On the other hand, the temporary storage of containers in the yard decouples the material flow of incoming and outgoing containers at the terminal. This study focuses on reducing the number of containers to be stored in the yard by direct container transshipment between modes of transport. Methodology: Based on a systematic literature review, approaches for skipping the storage phase at container terminals are identified. For this purpose, a classification scheme was developed and applied to academic publications. The classification scheme includes various criteria, such as the methodology and the research objective of the considered publications. Findings: The results show that in science, direct transshipment of containers at seaport terminals is mainly studied between ships. Furthermore, many studies do not focus exclusively on direct transshipment but consider it as a possible design alternative. Originality: Only a few studies have looked at skipping the storage phase on container terminals. An overview of existing studies on direct container handling between two modes of transport and skipping the storage phase does not yet exist.
urn:nbn:de:gbv:830-882.0200766; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Port Logistics